1970
DOI: 10.2151/jmsj1965.48.2_129
|View full text |Cite
|
Sign up to set email alerts
|

Stability of a Plane Parallel Flow with Variable Vertical Shear and Unstable Stratification

Abstract: A study is made of stability properties of perturbations superimposed on an unstably stratified plane parallel flow with variable vertical shear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
73
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(86 citation statements)
references
References 28 publications
13
73
0
Order By: Relevance
“…Asai (1972) investigated the nature of instability in unstably stratified shear flows turning the direction with height, which is a similar situation in this case. He showed that two di¤erent types of instability are obtained in the case of directional shear flows with points of inflection as in the unidirectional shear flow case shown in Asai (1970b). One is the shear-perpendicular mode driven primary by the vertical shear and the other is the shear-parallel mode driven by the buoyancy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Asai (1972) investigated the nature of instability in unstably stratified shear flows turning the direction with height, which is a similar situation in this case. He showed that two di¤erent types of instability are obtained in the case of directional shear flows with points of inflection as in the unidirectional shear flow case shown in Asai (1970b). One is the shear-perpendicular mode driven primary by the vertical shear and the other is the shear-parallel mode driven by the buoyancy.…”
Section: Discussionmentioning
confidence: 98%
“…Yagi (1985) and Yagi et al (1986) analyzed GMS images and upper-air sounding data and indicated that the axes of the transversal cloud bands were parallel to the vertical wind shear vector of horizontal winds. In addition, by applying the linear theory of the thermal instability in the vertical shear flow (Asai 1970a(Asai , 1970b(Asai and 1972, Yagi (1985) proposed that the transversal cloud bands were produced from longitudinal-mode (shear-parallel mode) roll convections. Recently, Shimizu and Tsuboki (2005) analyzed the transversal cloud band near the coast of the Hokuriku district on the basis of dual-Doppler radar observations.…”
Section: Introductionmentioning
confidence: 99%
“…These induced surface heterogeneities are the link between radiative transfer and buoyancy-driven convection (Lohou and Patton, 2014;Horn et al, 2015;Gronemeier et al, 2016). Our focus is therefore more on buoyancy-driven roll vortices in a linear shear environment (Asai, 1970) and less so on inflectionpoint instabilities. To that end, we omit cross-wind shear by neglecting Coriolis force and correspondingly neglect the horizontal turning of the wind as it would be the case in an Ekman boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…In such situations, the energy for the circulations comes from the buoyancy and, if of sufficient magnitude, the vertical wind shear organizes the resulting circulations to minimize shear in the cross-band direction, forming horizontal convective rolls (e.g. Kuo, 1963;Asai, 1970;Miura, 1986;Shirer, 1986). Instead of vertical wind shear, many authors use near-surface wind velocity to determine the band orientation.…”
Section: Introductionmentioning
confidence: 99%